First Tarsometatarsal Joint Fusion in Foot—A Biomechanical Human Anatomical Specimen Analysis with Use of Low-Profile Nitinol Staples Acting as Continuous Compression Implants - Andrew Sands; Ivan Zderic; Michael Swords; Dominic Gehweiler; Daniel Ciric; Christoph Roth; Christoph Nötzli; Boyko Gueorguiev (Medicina, 2023)
Background and Objectives: The aim of this study was to investigate under dynamic loading the potential biomechanical benefit of simulated first tarsometatarsal (TMT-1) fusion with low-profile superelastic nitinol staples used as continuous compression implants (CCIs) in two different configurations in comparison to crossed screws and locked plating in a human anatomical model. Materials and Methods: Thirty-two paired human anatomical lower legs were randomized to four groups for TMT-1 treatment via: (1) crossed-screws fixation with two 4.0 mm fully threaded lag screws; (2) plate-and-screw fixation with a 4.0 mm standard fully threaded cortex screw, inserted axially in lag fashion, and a 6-hole TMT-1 Variable-Angle (VA) Fusion Plate 2.4/2.7; (3) CCI fixation with two two-leg staples placed orthogonally to each other; (4) CCI fixation with one two-leg staple and one four-leg staple placed orthogonally to each other. Each specimen was biomechanically tested simulating forefoot weightbearing on the toes and metatarsals. The testing was performed at 35–37 °C under progressively increasing cyclic axial loading until construct failure, accompanied by motion tracking capturing movements in the joints. Results: Combined adduction and dorsiflexion movement of the TMT-1 joint in unloaded foot condition was associated with no significant differences among all pairs of groups (p ≥ 0.128). In contrast, the amplitude of this movement between unloaded and loaded foot conditions within each cycle was significantly bigger for the two CCI fixation techniques compared to both crossed-screws and plate-and-screw techniques (p ≤ 0.041). No significant differences were detected between the two CCI fixation techniques, as well as between the crossed-screws and plate-and-screw techniques (p ≥ 0.493) for this parameter of interest. Furthermore, displacements at the dorsal and plantar aspects of the TMT-1 joint in unloaded foot condition, together with their amplitudes, did not differ significantly among all pairs of groups (p ≥ 0.224). Conclusions: The low-profile superelastic nitinol staples demonstrate comparable biomechanical performance to established crossed-screws and plate-and-screw techniques applied for fusion of the first tarsometatarsal joint.